'Fear of contact': Police surveillance through social networks. Issue 4 (2nd October 2017) - Trottier, Daniel
ABSTRACT: This paper considers the adoption of social media monitoring (SMM) devices by police forces for surveillance purposes. In particular, it examines the use of MM devices in terms of technical, but also social and normative dimensions for police. While existing scholarship focuses on 'assemblages' within social networks that augment the scope and reach of policing institutions, such connectivity also provokes concern in relation to the distribution and augmentation of vulnerabilities. In accounting for the production, circulation, and consumption of SMM devices, this paper considers findings from a set of interviews with respondents overseeing the adoption of SMM devices in European police agencies. These interviews indicate that heightened reliance on both private and public partnerships, as well as unclear terms relating to the visibility of both social life and police work, further exacerbate concerns about the acceptability of such devices in practice.